Odpowiedź :
Odpowiedź:
a) (10- 2) * 2 = 8 * 2 = 16
b) 5 + 3 * 2 = 5 + 6 = 11
c) 12 : 6 * 2 = 2 * 2 = 4
d) 9 : 3 : 3 = 1
e) 10 + 2 * (3 + 2 : (1 + 1)) = 10 + 2 * (3 + 2 : 2) = 10 + 2 * (3 + 1) =
= 10 + 2 * 4 = 10 + 8 = 18
f) ( 2 * (3 - 1) + 6) : 5 = (2 * 2 + 6) : 5 = (4 + 6) : 5 = 10 : 5 = 2
Szczegółowe wyjaśnienie:
Odpowiedź:
Szczegółowe wyjaśnienie:
a)
(10 - 2)* 2 = 8 * 2 = 16
b)
5 + 3 * 2 = 5 + 6 = 11
c)
12 : 6 * 2 = 2 * 2 = 4
d)
9 : 3 : 3 = 3 : 3 = 1
e)
10 + 2 * [(3 + 2 : ( 1 + 1)] = 10 + 2 * (3 + 2 : 2) = 10 + 2 * ( 3 + 1) = 10 + 2 * 4 = 10 + 8 = 18
f)
[ 2* (3 - 1)+ 6 ] : 5 = (2 * 2 + 6) : 5 = ( 4 + 6) : 5 = 10 : 5 = 2